The ability of biochar and activated biochar as arsenic adsorbent / Munirah Abdullah Hadi - Abdullah Hadi, Munirah (Faculty of Plantation and Agrotechnology, 2016)
The experiment was conducted to investigated the ability of biochar and activated biochar as arsenic (As) adsorbent. Adsorptions of heavy metal such as arsenic (As) onto EFB biochar and EFB activated biochar have being studied using batch adsorption method. This study was carried out to examine the adsorption capacity of the EFB biochar and EFB activated biochar in removing arsenic (As). Batch adsorption method was conducted with different initial arsenic (As) concentrations to give different final equilibrium concentration as a function as solute adsorbed per gram of adsorbent. The potential adsorption by EFB biochar and EFB activated biochar for arsenic (As) removal was investigated to determine the efficiency of the biochar and activated biochar as the adsorbents. The initial concentrations was highest were equilibrium relationships between adsorbent and adsorbate which is described by adsorption isotherms model which give the capacity of adsorbent for an adsorbate. Result shows the adsorption rate increased with increased of level concentration of arsenic (As). Results indicated that the EFB biochar is locally available, low cost adsorbent and treated as economically viable for the removal of metal ions from mining or agriculture effluents.